General educators’ attitude towards students with Autism Spectrum Disorder (ASD) in general education: a scoping review / Norfezah Md Nor and Nur Afiqah Mahzan - Md Nor, Norfezah; Mahzan, Nur Afiqah (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2023)
General educators’ attitude towards their student plays a significant role in shaping their students to success. General educators commonly associate it with having no or basic experience in handling special need students, hence the poor attitudes towards them. The current scoping review is solely to focus on the effects of general educators’ attitude towards students with ASD. Three databases searched yielded ten relevant articles. There were mixed findings regarding the impact of having minimum experience in handling special needs students and positive attitudes. In summary, general educators’ attitude towards the inclusion of students with ASD in general education setting is positive but we highlight the effects to improve general educators’ attitude so the experience of students with ASD in general’s education setting is better and acceptable. Further research is needed to study general educators’ attitude towards other disabilities other than ASD.